Need for resuming sports and physical activity for children and adolescents following COVID-19 infection - Calcaterra, G.; Fanos, V.; Cataldi, L.; Cugusi, L.; Crisafulli, A.; Bassareo, P. P. (Sport Sciences for Health, 2022)
Introduction: A decline in sports activities among children and adolescents was noted during the stay-at-home restrictions imposed by COVID-19. With the easing of restrictions, physical activities are being resumed. Evidence acquisition: A data search was conducted to identify the role of parents in resuming sporting activities, the risks and benefits of doing so, the physical examination to be conducted prior to physical activity, the existence of guidelines/protocols for return to sports and physical activity, the role of comorbidities in influencing the restart of the same. Evidence synthesis: Parents should consult the child`s physician prior to allowing he/she to resume physical exercise. In preparation for this, a careful physical examination should be performed. Children with COVID-19, even if asymptomatic, should not resume any physical activity until at least 10 days after testing positive. Those with moderate or severe COVID-19 should be referred for cardiological evaluation. The level of activity should be resumed gradually, as per the GRTP protocol. Athletes with a positive COVID-19 test in the presence of concomitant medical conditions (diabetes, cardiovascular or respiratory or renal disease) should undergo medical evaluation prior to adhering to a GRTP. Those with complicated COVID19 infection or long Covid may need additional investigations. Conclusions: While there is no doubt that it will bring multiple benefits in terms of general health, returning to play sport should be gradual and preceded by an accurate physical examination in those young subjects previously affected by the coronavirus disease, especially when their heart and/or lungs and/or kidneys were affected.